Clinical Characteristics and Outcome in Patients with Sphenoid Allergic Fungal Disease - Hisham B. Alem (Journal of King Abdulaziz University: Medical Sciences, 2023)
Sphenoid Allergic Fungal Disease is an uncommon disease, usually non-aggressive course, as reported in the literature. It is usually undiagnosed because of its atypical presentation. This series reports four cases of Sphenoid Allergic Fungal Disease presenting with distinct symptoms. This article describes the clinician’s experience in the diagnosis and treatment of Sphenoid Allergic Fungal Disease. This article also stresses the importance of competency and expertise of the clinician to be more suspicious of the Sphenoid Allergic Fungal Disease in their routine clinical practice as it is not a usual diagnostic condition. This four-case series will also explain the importance of various investigative procedures and radiological fi ndings to be incorporated as required for diagnosing and treating the cases of Sphenoid Allergic Fungal Disease.